Snailfishes of the genus Careproctus (Perciformes: Liparidae) with a reduced pelvic disk: three new species and new records from the western North Pacific with comments on their phenotypic diversity - Kai, Yoshiaki; Matsuzaki, Koji; Mori, Toshiaki; Pitruk, Dmitry L.; Misawa, Ryo; Tashiro, Fumihito (Zootaxa, 2024)
A taxonomic review of the snailfish genus Careproctus (Liparidae) with a reduced pelvic disk—the Careproctus gilberti species group—from the western North Pacific recognized three new species from the southern Sea of Okhotsk, and confirmed the validity of Careproctus gilberti, Careproctus mederi, Careproctus ostentum, and Careproctus parvidiscus. One of the newly described species, Careproctus longibarbatus sp. nov., had been previously confused with C. mederi, but was readily distinguishable on the basis of counts of vertebrae (61–66 vs. 57–63), dorsal- (56–60 vs. 52–56) and anal-fin rays (50–54 vs. 47–52), as well as length of the pectoral fin lower lobe (extending past anus vs. not reaching anus) and color of the peritoneum (dark vs. pale with black dots). Careproctus barbatulus sp. nov. and Careproctus spinulosus sp. nov. were diagnosed by pectoral fin lower lobe length, anus position, and vertebral, and dorsal- and anal-fin ray counts. The validities of the three new species were also confirmed by mitochondrial sequence data. Careproctus mederi was redescribed based on specimens from the southern Sea of Okhotsk, representing the first Japanese, as well as southernmost record of the species. Furthermore, the full description of an unidentified Careproctus species, most similar to C. gilberti, from the Pacific coast of Hokkaido was provided. Significant morphological variation within the C. gilberti species group, possibly resulting from reproductive interference among sympatric species, was also discussed.